2022
DOI: 10.3389/fonc.2022.1042493
|View full text |Cite
|
Sign up to set email alerts
|

The consistencies and inconsistencies between distal cholangiocarcinoma and pancreatic ductal adenocarcinoma: A systematic review and meta-analysis

Abstract: ObjectiveTo evaluate the consistencies and inconsistencies between distal cholangiocarcinoma (DCCA) and pancreatic ductal adenocarcinoma (PDCA) regarding their biological features and long-term prognosis.MethodsPubMed, the Cochrane Library, and EMBASE were searched to find comparative studies between DCCA and PDCA. RevMan5.3 and Stata 13.0 software were used for the statistical analyses.ResultsEleven studies with 4,698 patients with DCCA and 100,629 patients with PDCA were identified. Pooled results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Interestingly, dCCA had more favorable tumor pathological features and long-term prognosis than patients with PDAC. On the other hand, patients with dCCA suffer more frequently from postoperative complications and especially postoperative pancreatic fistula [79]. These findings further corroborate the idea that a correct differential diagnosis is crucial for addressing the best therapeutic strategies.…”
Section: Clinical Cluessupporting
confidence: 71%
“…Interestingly, dCCA had more favorable tumor pathological features and long-term prognosis than patients with PDAC. On the other hand, patients with dCCA suffer more frequently from postoperative complications and especially postoperative pancreatic fistula [79]. These findings further corroborate the idea that a correct differential diagnosis is crucial for addressing the best therapeutic strategies.…”
Section: Clinical Cluessupporting
confidence: 71%
“…A lymphadenectomy along with the hepatoduodenal ligament combined with partial hepatectomy has been strongly recommended as the standard surgical procedures for patients with progressive GBC disease. A clear margin without residual disease microscopically or macroscopically has been proved to be closely-associated with improved survival than those with positive margin 3 , 9 , 12 14 , 17 , 36 , 44 , 46 , 48 , 49 , 52 , 73 , which was also validated in our synthetic results with an extremely significant P -value combined with a high level of risk of death in terms of univariate analysis (HR=2.90, P <0.00001) and multivariate analysis (HR=2.28, P <0.00001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some researchers indicated that an elevated preoperative CA199 level indicated worse prognosis in postsurgical GBC patients 9 11 . Some easily-ignored predictors, such as age 12 , 13 and the level of preoperative fibrinogen level 14 , have also been recommended but not fully evaluated. Just as our previous series indicated that the whole biliary tract was surrounded by dense neural network, it might serve as another potential metastatic route for GBC patients 15 and prognostic significance of peri-neural invasion has also been validated in numerous previous publications 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Moreover, due to the inherent operational reasons of this examination method, many patients' feelings of pain during the examination lead to many problems with their actual situation. [18][19][20][21] PDCA management mode is a new management concept proposed by a management expert in the United States, Dai Ming. It mainly includes 4 steps, namely, P (plan), D (implementation), C (inspection), and A (treatment).…”
Section: Discussionmentioning
confidence: 99%
“…[15–17] Moreover, due to the inherent operational reasons of this examination method, many patients’ feelings of pain during the examination lead to many problems with their actual situation. [18–21]…”
Section: Discussionmentioning
confidence: 99%